A new multilevel inverter topology based on switched-capacitor technique - Saifullah Kakar; S. M. Ayob; M. Saad Bin Arif; N.M. Nordin; Z. Daud; R. Ayop (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a new multilevel inverter based on the switched-capacitor technique. The topology aims for renewable energy and fuel cell applications that demand high magnitude output ac voltage. This configuration of the inverter can produce a total of thirteen voltage levels using a single DC source. The topology features voltage boosting with a triple gain of the input voltage source without utilizing a boost DC-DC converter. Furthermore, the voltages of the capacitors are self-balanced at any desired voltage level during each cycle. Therefore, auxiliary circuits are no longer needed. A comparative study of the presented inverter with the classical topologies and recently introduced topologies has been done in power switches, driver circuits, blocking voltage of the switches, and boosting the input voltage. A simple fundamental switching scheme is applied to the proposed topology to validate the viability of the topology.